TOTAL FLAVONOID CONTENT OF KAPUL FRUIT PEEL EXTRACT (Baccaurea macrocarpa) BASED ON SOLVENT TYPE VARIATION USING UV-VIS SPECTROPHOTOMETRY - Rahmadani Rahmadani; Risa Supriningrum; Hayatus Sa'adah (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
The solvent type plays a crucial role in influencing the extraction of active compounds from natural materials. The peel of kapul fruit (Baccaurea macrocarpa) is known to contain flavonoid compounds with notable antibacterial properties. This study aimed to quantify the total flavonoid content in kapul fruit peel extract by evaluating the effects of different solvent types using the UV-Vis spectrophotometric method. The analysis revealed the presence of secondary metabolites, including alkaloids, saponins, and flavonoids. The total flavonoid content of the kapul fruit peel extract varied significantly across different solvents: 4.7238 ± 0.5807 mgQE/g for ethanol, 2.9699 ± 0.1539 mgQE/g for ethyl acetate, and 2.0417 ± 0.4236 mgQE/g for n-hexane. Statistical analysis demonstrated a significant difference in flavonoid content among the three solvent extracts. These results highlight the importance of solvent selection in maximizing the extraction efficiency of flavonoids from kapul fruit peel, which may have implications for its potential therapeutic applications.